1980
DOI: 10.1104/pp.66.6.1027
|View full text |Cite
|
Sign up to set email alerts
|

Early Events in the Infection of Soybean (Glycine max L. Merr) by Rhizobium japonicum

Abstract: The infectible cells of soybean roots appear to be located at any given time just above the zone of root elongation and just below the position of the smallest emergent root hairs. The location of infectible cells on the primary root at the time of inoculation was inferred from the position of subsequent nodule development, correcting for displacement of epidermal cells due to root elongation. Marks were made on the seedling growth pouches at the time of inoculation to indicate the position of the root tip and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
231
0
21

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(264 citation statements)
references
References 6 publications
12
231
0
21
Order By: Relevance
“…Such molecules are involved in cell-cell interactions, notably in plant-microorganism and plantpest interactions (2,6,17,27). The way elicitors of ethylene control biochemical and molecular events related to plant diseases is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Such molecules are involved in cell-cell interactions, notably in plant-microorganism and plantpest interactions (2,6,17,27). The way elicitors of ethylene control biochemical and molecular events related to plant diseases is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to skl, the sunn mutant has a supernumerary nodulation phenotype (Schnabel et al, 2005) but, unlike skl, sunn nodules form adjacent to xylem poles (Penmetsa et al, 2003). The combined negative action of ethylene and AON pathways leads to a tight restriction of the developmental competency to form symbiotic nodules (Bhuvaneswari et al, 1980;Sargent et al, 1987;Kassaw et al, 2015). Indeed, when a root is inoculated, nodule formation results from infections initiated in young, developing root hairs, and competency for further root hair infection and nodule organogenesis diminishes rapidly due to the activation of the local ethylene/EIN2-dependent (Penmetsa and Cook, 1997) and systemic CLE/AON-dependent responses (Kassaw et al, 2015).…”
mentioning
confidence: 99%
“…In legumes, the formation of nitrogen (N) fixing root nodules and lateral roots (LRs) predominantly determine root system architecture. Cells that become competent for root nodule and LR formation are both similarly located close to the root apical meristem (RAM; Bhuvaneswari et al, 1980;Sargent et al, 1987;Herrbach et al, 2014). The N 2 -fixing nodules induced by rhizobia provide considerable N to legumes and enable them to grow in N-poor environments.…”
mentioning
confidence: 99%
“…The suppressive response was not elicited by heterologous or by dead homologous bacteria (7). Based on the short distance between the regions of maximum nodulation and suppressed nodulation, it was inferred that the suppressive response was elicited very rapidly, within an hour or so, by the first inoculum (2,7). More recent studies (3), however, revealed that the initiation of infection in the younger regions was not suppressed.…”
mentioning
confidence: 93%
“…In soybean (Glycine max L.), nodulation frequency decreases considerably down in the younger regions of the roots (1,2). Previous studies (7), involving double inoculation of the roots, showed that the nodulation in the younger regions of soybean root was suppressed by prior inoculation of more mature regions of the root.…”
mentioning
confidence: 99%